Breast cancer with diabetes insipidus - Dogan, M.; Karakilic, E.; Oz, I.I.; Zorlu, F.; Akbulut, H. (Experimental Oncology, 2008)
Diabetes insipidus (DI) is a rare clinical condition, which is usually caused by neurohypophyseal or pituitary stalk infiltration in cancer patients. Case report: we present a 62-year old metastatic breast cancer woman with DI. She admitted to the hospital because of nausea, vomiting, polyuria and polydipsia, while she was on no cytotoxic medication. She had no electrolyte imbalance except mild hypernatremia. The CT scan of the brain yielded a suspicious area in pituitary gland. A pituitary stalk metastasis was found on magnetic resonance imaging (MRI) of pituitary. Water deprivation test was compatible with DI. A clinical response to nasal vasopressin was achieved. Conclusions: Cancer patients who have symptoms such as nausea, vomiting, polyuria and polydipsia while they are not on chemotherapy should be evaluated for not only metabolic complications like hypercalcemia but also posterior pituitary or stalk metastasis MRI could be the choice of imaging for pituitary metastasis.